Pengembangan E-Modul Literasi Berbasis Model Problem Based Learning untuk Meningkatkan Kemampuan Literasi Siswa SD Aceh Besar: Development of a Literacy E-Module Based on a Problem-Based Learning Model to Improve the Literacy Skills of Elementary School Students in Aceh Besar - Halimah Halimah; Syarfuni Syarfuni; Irfandi Irfandi (ITScience (Information Technology and Science), 2026)
Literacy skills are an important basic competency for elementary school students in supporting learning success. However, in reality, students’ literacy skills remain relatively low due to teacher-centered instruction and the limited use of innovative, interactive learning media. Therefore, it is necessary to develop e-modules for literacy based on Problem-Based Learning (PBL) to improve students’ literacy skills. This study aims to develop literacy e-modules based on Problem-Based Learning (PBL) that are valid, practical, and effective in improving elementary school students’ literacy skills. The method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The study was conducted at SD Negeri 1 Pagar Air, Aceh Besar Regency, with fifth-grade students as subjects. Data collection techniques included interviews, observations, questionnaires, and literacy tests, including pretests and posttests. The results showed that the developed e-module was categorized as very practical, with validation percentages of 92% among material and media experts, 88% among teachers, and 84% among students. Furthermore, there was a significant increase in students’ literacy skills, as indicated by an average pretest score of 58.8, rising to 99.8 on the posttest. Data analysis also showed that the data were normally distributed and homogeneous, and that there were significant differences between the pretest and posttest results. Therefore, the Problem-Based Learning (PBL) e-module was deemed feasible and effective as a learning medium for improving elementary school students’ literacy skills.